Niveles De Ansiedad Post Pandemia En Estudiantes De Grado Quinto De Primaria En Una Institución Educativa De La Ciudad De Ibagué (2022)
The main objective of this research project for its development was to determine the level and nature of post-pandemic anxiety in fifth grade students in an educational institution in the city of Ibague, taking as a previous for its study at a general level if these problems count. with “Low” “Moderate” or “High” characteristics within the population. The methodology used for this research was carried out through a quantitative approach; Like, field research through the application of the Manifest Anxiety Scale in children CMAS-R 2 and a Likert-kind poll for parents, with a sample of 24 participants. As a result, it was possible to show that in general anxiety, boys are the most affected since they are at moderate and high levels, while girls tend to be at moderate and low levels. Finally, the conclusions of this research are established, which allowed us to identify that for parents the pandemic affected children's anxiety, that is, there was an increase in levels, and for children there was too an increase, but in less proportion.